Development and validation of a dynamic mass-balance prediction model for indoor particle concentrations in an office room. (January 2022) - Park, Soo Bhin; Park, Ju-Hyeong; Jo, Young Min; Song, Doosam; Heo, Sujeong; Lee, Tae Jeong; Park, Sowoo; Koo, Junemo
Abstract: The Korean government recommends intermittent operation of air purifiers (APs) as a measure to maintain indoor particulate matter (PM) concentrations below the mandatory standards and reduce exposure to indoor PM2.5 (PM with a diameter smaller than 2.5 μm). However, there is no guideline to inform occupants of when and how long APs should be operated to comply with the standards. In this study, we developed a dynamic mass-balance model to predict indoor PM concentrations in an office considering penetration of outdoor particles, change in number of occupants, and operational status of the AP. The model fit and prediction accuracies were verified using the American Society for Testing and Materials (ASTM) D 5157 criteria and the k-fold validation technique. We observed that indoor PM2.5 concentrations were determined by infiltration of outdoor PM2.5, and indoor generation/resuspension by occupants and removal. For PM2.5-10 (2.5 μm < diameter <10 μm), the indoor concentrations were determined by interior door access and indoor generation/resuspension. The operation of an AP effectively decreased indoor PM2.5 concentration but not PM2.5-10 . We found that our model accurately predicted indoor PM concentrations. Therefore, using the developed model, a guideline may recommend: 1) start the AP when the predicted indoor PM2.5 concentrations under no AP operation approached the standard (e.g., 90% of the standard); and 2) stop the AP when the indoor PM2.5 concentration predicted under the assumption of no AP operation fell below the standard (e.g., 80% of the standard). Highlights: A dynamic mass-balance model of indoor particle concentrations was developed. Model accuracy was verified using the ASTM D 5157 criteria. Particle penetration with air infiltration was the main source of indoor PM2.5 Occupants' door access was the main contributor of indoor coarse particle. Impact of air purifier operation on indoor particle concentration was scrutinized.